Designing the cross-linked network to tailor the mechanical fracture of elastomeric polymer materials. (14th June 2022) - Li, Ke; Li, Ziwei; Liu, Jun; Wen, Shipeng; Liu, Li; Zhang, Liqun
Abstract: Understanding the elastomer fatigue mechanism under a cyclic loading is of vital importance in fabricating elastomer nanocomposites with high performance. Based on the microstructural evolution and the mechanical response under the dynamic periodic loading, the molecular mechanism about the effect of cross-linked network (including crosslink bond type and crosslink density) on the fatigue resistance was examined by adopting coarse-grained molecular dynamics simulation. The result shows that the elastomer molecular chains are more prone to disentangle and orientate in the polysulfide system, compared to those monosulfide and disulfide systems. Rubber molecular chains can uniformly sustain the external tensile stress in the polysulfide system, which is beneficial to avoid the rapture of rubber molecules. With the increase of the crosslink density, increase to a plateau. In the presence of saturated network size, an optimum crosslink density and distribution for rubber nanocomposites appears, avoiding the possibilities of rubber molecule rupture. This work provides some insights on understanding the relationship between the cross-linked network and the fatigue performance of the rubber composites at the molecular level, expecting to provide some guidelines for preparing elastomeric materials with high fatigue resistance. Graphical abstract: Image 1 Highlights: Investigation on the microstructural evolution and the mechanical response of elastomer under the dynamic periodic loading by MD simulation. Quantified the size of the cross-linked network by the molecular weight (Mc, Mcn, Mtn ) of the network chain. The polysulfide crosslinker is conducive to the disentangle and orientate of elastomer chains which inhibits the rupture of the chemical bonds. The optimal crosslinking density corresponds to saturated crosslinking network size.